Makam dan Masjid dalam Budaya Masyarakat Betawi - Juwono, Sudarmawan (TAJDID, 2017)
In the perspective of architectural science and social culture, the existence of residential layout is an indicator of social dynamic of its society. This research studies about a phenomenon of the existence of grave and mosque which still exists from residential area razing in the middle of modern area Mega Kuningan Jakarta. The existence of these both sacred places are very interesting to be studied and analyzed in the context of local Islamic culture resistance encountering the urbanization condition generated by global power. The question raised in this study, how is the existence of grave and mosque as the embodiment of Islamic culture resistance of kampung Betawi society. The finding in this study indicates that the spatial existence is the limit of Islamic culture of kampung society in the process of urbanization.